Accessibility Evaluation of Learning Object Repositories - Londono-Rojas, Luis; Vicari, Rosa Maria; Duque-Mendez, Nestor (2022 XVII Latin American Conference on Learning Technologies (LACLO), 2022)
Currently, the use of learning objects is an alternative that offers the possibility that a subject can be presented in different forms and formats, which allows the material to be adjusted to the needs of students, however, if the repositories that are the platforms that store and make them available do not satisfy an acceptable level of accessibility, then the learning objects in many cases cannot be used by students. For this reason, the objective of this paper is to review the accessibility of twenty learning object repositories based on the WCAG using three automatic accessibility validators and one short manual evaluation, to identify the accessibility level, the accessibility errors and the accessibility alternatives provided.